Elecciones generales de 2019 en Twitter: eficacia de las estrategias comunicativas y los debates televisados como motor del discurso social - Abuín Vences, Natalia; García-Rosales, Daniel-Francisco (El profesional de la Información, 2020)
This research analyzes candidates and political parties electoral campaign on Twitter that have obtained greater parlia-mentary representation in the general elections held in April 2019 in Spain. The main objective of this work is to analyze the influence of the electoral debates in the publications of the candidates and political parties on Twitter, to find out if they have a greater impact and enhance social discourse. We also aim to determine what type of messages and strategies have greatest impact on Twitter. The methodology used to achieve these goals was a quantitative, qualitative, explanatory and cross-sectional content analysis. To carry it out, a sample composed by 745 tweets was selected from those that reached more than 500 retweets, published by parties (PSOE, PP, Ciudadanos, Unidos Podemos and Vox) and candidates (Pedro Sánchez, Pablo Casado, Albert Rivera, Pablo Iglesias and Santiago Abascal) during the election campaign (21A).The results suggest that televised debates act as true catalysts for social conversation, so the publications made by both, the parties and the candidates themselves, during the television broadcast of these events achieve a greater impact among followers, than those that are not linked to such events. Likewise, it is demonstrated that parties and candidates born in the heyday of social media, get a greater diffusion of their messages, because they have opti-mized their strategies in social networks, something that have not yet been achieved by the formations accustomed to conventional mass media. © 2020, El Profesional de la Informacion.
Spanish general election 2019 on twitter: Effectiveness of communicative strategies and televised debates as an engine of social discourse
Keywords: comunicación política; campañas electorales; elecciones; medios sociales; redes sociales; Twitter; candidatos; partidos políticos; debates televisivos; debates; televisión; TV; España; candidates; debates; elections; electoral campaigns; political communication; political parties; social media; social networks; Spain; television; television debates; Scopus; JCR